2006
DOI: 10.1016/j.clpt.2005.12.137
|View full text |Cite
|
Sign up to set email alerts
|

PII-12Absolute bioavailability of vildagliptin in healthy subjects

Abstract: OBJECTIVES Vildagliptin (V) is a potent and specific DPP‐4 inhibitor, which is developed for treatment of type 2 diabetes (T2D). The objective of this study was to investigate the absolute bioavailability (F) of V after oral and intravenous (iv) administration of V. METHODS This was an open label, single‐dose, randomized, cross‐over study in healthy volunteers. Thirteen subjects were enrolled and 12 completed the study. Each subject was randomly assigned to receive one of the two treatments in a sequential man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Renal clearance has been reported as 217 mL/min for vildagliptin (40) and 388 mL/min for sitagliptin (37) and is estimated to account for approximately a third of total body clearance (40). A study of sitagliptin in patients with renal insufficiency has shown that AUC and C max values increase with the level of insufficiency (42).…”
Section: Introductionmentioning
confidence: 99%
“…Renal clearance has been reported as 217 mL/min for vildagliptin (40) and 388 mL/min for sitagliptin (37) and is estimated to account for approximately a third of total body clearance (40). A study of sitagliptin in patients with renal insufficiency has shown that AUC and C max values increase with the level of insufficiency (42).…”
Section: Introductionmentioning
confidence: 99%
“…Vildagliptin is extensively distributed into tissues at steady state with a large volume of distribution (71 L). The primary route of elimination of vildagliptin is metabolism via hydrolysis of the cyano moiety, which accounts for approximately two thirds of the elimination of the drug; one third of an absorbed dose is excreted unchanged by the kidneys 20 …”
mentioning
confidence: 99%
“…The pharmacokinetics of vildagliptin have been studied in healthy subjects and in patients with type 2 diabetes. Vildagliptin is rapidly absorbed with an absolute bioavailability of 85% 17 . Maximum plasma concentration (C max ) occurs 1 to 2 hours after oral administration, and the elimination half‐life is around 2 hours.…”
mentioning
confidence: 99%